Computational Systemic Biology for Toxicity Studies: A Mini Review of Previously Published Articles - Yilkal Tariku Belay (Journal of Advanced Pharmaceutical Science And Technology, 2022)
The strategy for safe drug discovery and development has limited clinical success as compared to wasted time and resources annually. This is due to the fact that the results of multiphase preclinical trials are less likely to make an accurate early prediction on the safety of test compounds to progress into the clinic as a valuable therapeutic agent. A lot of time and resources has been wasted in the multistage processes of drug discovery and development that does not work at the end of the procedure every year. During pre-marketing stage, for instance, the number of unsuccessful clinical trials are greater than the successful one because of safety issues. A toxicity study at different stages of preclinical and clinical trials is a routine procedure to investigate the undesirable side effects of test compounds being manifested on the natural processes of living things. It deals with the effect and mechanism of toxicity of test compounds that triggers different biological responses on different organ systems. The biological responses that would be manifested as a result of interaction between the receptors and active molecules of a test compound could be desirable pharmacological effect or undesirable side effect or both responses are manifested simultaneously depending on the selectivity or specificity of the molecule of a test compound for its receptor subtype which makes safe drug discovery and development very challenging. The response efficiency of the body (the net outcome of the body’s biological reaction against the side effect) would determine the potency of a test compound to manifest undesirable pharmacologic effect. In other words, the amount of a drug required to cause a biological harm or injury depends on the magnitude of the body’s biological reaction in which the immune response plays a great pharmacological role by neutralizing and harmonizing xenobiotics with the biological molecules. The dose of a test compound at 100 mg/kg body weight, for instance, could be lethal to some of the study animals while it is still non-lethal to some other study animals depending on the response efficiency of the body. The immune system is well connected to each and every biological systems of the body which allows it to detect undesirable side effects being manifested through immunoglobulins signalling and activation mechanisms. This complex communication network helps to localize the diverse side effects of a test compound being manifested on different organ systems into the immune system which makes a toxicity study relatively simple to monitor. The cellular immune system becomes active following the molecule-receptor interaction and start producing antibodies which is also known as immunoglobulins to protect bodily harm and destruction. Under normal biological circumstances, the amount of immunoglobulins produced by the cellular immune system following exposure to a test compound is proportional to the number of harmful molecules interacted with its receptor subtype. Thus, with the reference to the changes in the immune response against the administered dose, it would be able to deal with the diverse undesirable side effects of a test compound being manifested on treated study animals using computational systemic biology.
Keywords: Pharmacology